Functional Analysis of Maize Silk-Specific ZmbZIP25 Promoter - Li, Wanying (Int J Mol Sci, 2018)
ZmbZIP25 (Zea mays bZIP (basic leucine zipper) transcription factor 25) is a function-unknown protein that belongs to the D group of the bZIP transcription factor family. RNA-seq data showed that the expression of ZmbZIP25 was tissue-specific in maize silks, and this specificity was confirmed by RT-PCR (reverse transcription-polymerase chain reaction). In situ RNA hybridization showed that ZmbZIP25 was expressed exclusively in the xylem of maize silks. A 5′ RACE (rapid amplification of cDNA ends) assay identified an adenine residue as the transcription start site of the ZmbZIP25 gene. To characterize this silk-specific promoter, we isolated and analyzed a 2450 bp (from −2083 to +367) and a 2600 bp sequence of ZmbZIP25 (from −2083 to +517, the transcription start site was denoted +1). Stable expression assays in Arabidopsis showed that the expression of the reporter gene GUS driven by the 2450 bp ZmbZIP25 5′-flanking fragment occurred exclusively in the papillae of Arabidopsis stigmas. Furthermore, transient expression assays in maize indicated that GUS and GFP expression driven by the 2450 bp ZmbZIP25 5′-flanking sequences occurred only in maize silks and not in other tissues. However, no GUS or GFP expression was driven by the 2600 bp ZmbZIP25 5′-flanking sequences in either stable or transient expression assays. A series of deletion analyses of the 2450 bp ZmbZIP25 5′-flanking sequence was performed in transgenic Arabidopsis plants, and probable elements prediction analysis revealed the possible presence of negative regulatory elements within the 161 bp region from −1117 to −957 that were responsible for the specificity of the ZmbZIP25 5′-flanking sequence.